MENINGKATKAN KEDISIPLINAN GURU SMP AWAL KARYA PEMBANGUNAN GALANG MELALUI PENERAPAN PENCATATAN PIKET - Dian Angraini; Zalmi Zalmi (Jurnal Dedikasi Pendidikan, 2021)
This research was conducted to implement strict and sustainable picket recording for the teachers of the SMP Awal Karya Pembangunan Galang, Deli Serdang Regency. This research is a school action research carried out for two cycles in the teachers of the SMP Awal Karya Pembangunan Galang in the 2018-2019 academic year. This research was conducted in two cycles, each cycle was conducted in one week. This research was conducted by observing the teacher's attendance at the first hour and the teacher's return at the last hour. The results of this study are: there is an increase in the discipline of the presence of teachers who enter at the first hour according to the schedule, and an increase in the discipline of teachers leaving the class at the last hour also according to the schedule